GRAFOLOGIA COMO FERRAMENTA DE AVALIAÇÃO DE POTENCIAL DE LIDERANÇA NA GESTÃO DO PROCESSO SELETIVO NAS ORGANIZAÇÕES - Pimenta, Mônica Barciela (2011)
In such a globalized world where changes are constant, companies must create differentiated and competitive procedures. The role of leadership is indispensabel for achieving strategic outcomes, as an agent that manages the changes and extract the potential of a team. Therefore it is necessary estrategy people managment, to attract and retain talented professionals.This research identified in the management of the selection process of organizations, the tools used in the search for professionals with leadership potential. Graphology, as an evaluation tool in a selection process, enables the human resources departament to provide top executives in the choice of professionals. This research is exploratory and bibliographical, concerning respectively the ends and means. It s a field study, realized by a structured questionnaire will be used of survey, in five industries of the state of Rio de Janeiro.